Ca2+-modulated ROS-GC1 transduction system in testes and its presence in the spermatogenic cells - Jankowska, Anna; Sharma, Rameshwar K.; Duda, Teresa (Frontiers in Molecular Neuroscience, 2014)
ROS-GC1 belongs to the Ca2+-modulated sub-family of membrane guanylate cyclases. It primarily exists and is linked with signaling of the sensory neurons – sight, smell, taste and pinealocytes. Exceptionally, it is also present and is Ca2+-modulated in the non-neuronal cells, the sperm cells in the testes, where S100B protein serves its Ca2+ sensor. The present report demonstrates the identification of an additional Ca2+ sensor of ROS-GC1 in the testes, neurocalcin . Through mouse molecular genetic models, it compares and quantifies the relative input of the S100B and neurocalcin  in regulating the Ca2+ signaling of ROS-GC1 transduction machinery, and via immunochemistry it demonstrates the co-presence of neurocalcin  and ROS-GC1 in the spermatogenic cells of the testes. The suggestion is that in more ways than one the Ca2+-modulated ROS-GC1 transduction system is linked with the testicular function. This non-neuronal transduction system may represent an illustration of the ROS-GC1 expanding role in the trans-signaling of the neural and non-neural systems.